Correlação entre os resultados de tração a quente e fluência para o cobre comercialmente puro - Dias, Cayo Roberto Ferreira (2011)
Hot tensile test data were correlated with creep data, in commercially pure copper, using a recently proposed criterion for the analysis of these two kinds of tests at high temperature. The criterion considers the equivalence between the following parameters in each case: deformation rate, ultimate tensile stress, time taken to reach the ultimate tensile stress, in tensile tests respectively with: minimum creep rate, applied stress, rupture time, in creep tests, at a certain test temperature. In tension, the material was tested in the temperature range from 250 to 550°C, using constant deformation rates varying from 1x10-5 s-1 to 0.208 s-1. In creep the temperature range varied from 250 to 525°C with stresses varying from 7.5 to 60 MPa at constant load. The conversion of the hot tensile data to creep data made possible the common analysis of all the results according to typical relations pro-posed by several authors in creep literature: Norton, Arrhenius, Zener-Hollomon and Monkman-Grant, with determination of the corresponding parameters in each case. The data were also analyzed according to four different parameterization methods commonly mentioned in the traditional creep literature for data extrapolation: Larson-Miller, Orr-Sherby- Dorn, Manson-Succop and Manson-Haferd. With exception of the Larson-Miller method, all the attempts for data correlation of hot tensile and creep tests produced excellent results. In addition to the correlation between these two kind of tests, a detailed analysis of the results of hot tensile and creep tests was carried out, separately, with discussion of the mechanical behavior of the commercially pure copper in each case.